2022
DOI: 10.1101/2022.01.25.477716
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of the orbitofrontal cortex in creating cognitive maps

Abstract: We use internal models of the external world to guide behavior, but little is known about how these cognitive maps are created. The orbitofrontal cortex (OFC) is typically thought to access these maps to support model-based decision-making, but it has recently been proposed that its critical contribution may be instead to integrate information into existing and new models. We tested between these alternatives using an outcome-specific devaluation task and a high-potency chemogenetic approach. We found that sel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
2
1
0
Order By: Relevance
“…In any case, the overall results from monkeys with damage to the OFC indicate that this region is not directly involved in discriminating novel from familiar stimuli. These results align with recent evidence in rats suggesting that inactivation of the OFC did not impair novel object recognition memory performance (Costa et al, 2022). The current results also support growing evidence that areas 11/13 of the OFC, the intended lesion locations, do not play an essential role in whether a stimulus is rewarded (i.e., reward contingency; Bachevalier et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…In any case, the overall results from monkeys with damage to the OFC indicate that this region is not directly involved in discriminating novel from familiar stimuli. These results align with recent evidence in rats suggesting that inactivation of the OFC did not impair novel object recognition memory performance (Costa et al, 2022). The current results also support growing evidence that areas 11/13 of the OFC, the intended lesion locations, do not play an essential role in whether a stimulus is rewarded (i.e., reward contingency; Bachevalier et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Individual neurons appear to respond to either information or external reward in the monkey orbitofrontal cortex (OFC) 23 , suggesting the presence of distinct representations of intrinsic and extrinsic value. These separate representations are consistent with a role for OFC in encoding distinct task variables of value that are integrated downstream to motivate a combined valuebased choice 30,33,34,36,[39][40][41][42][43][44] .…”
Section: Introductionsupporting
confidence: 66%
“…We used a shorter cue-reward interval to better enable subjects to predict reward delivery. This conditioning has also been shown to engender the encoding of identity-specific cue-reward memories as evidenced by sensitivity of the conditional goal-approach response to devaluation of the predicted reward 44 . Again, we found that BLA dopamine is associated with cue-reward learning (Figure 1k-l).…”
Section: Resultsmentioning
confidence: 99%